2022
DOI: 10.3389/fpls.2022.1004833
|View full text |Cite
|
Sign up to set email alerts
|

Potential of mineral-solubilizing bacteria for physiology and growth promotion of Chenopodium quinoa Willd

Abstract: Nutrient deficiency in wild plant species, including quinoa (Chenopodium quinoa Willd), can be overcome by applying mineral-solubilizing bacteria. Quinoa is a gluten-free, nutritious food crop with unique protein content. The present study aimed to characterize mineral-solubilizing rhizobacterial strains and to evaluate their plant growth-promoting potential in quinoa seedlings. More than sixty rhizobacterial strains were isolated from the quinoa rhizosphere and found eighteen strains to be strong phosphate so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 105 publications
1
5
0
Order By: Relevance
“…Inoculation with bacterial strains enhances growth and growth-related attributes of cotton, owing to different direct and indirect growth-promoting traits. In present studies, co-inoculation with phosphate and Zn solubilizing strains enhanced growth and yield parameters of cotton crop that might be due to catalase activity, urease activity, phytohormone production, exopolysaccharides production [59] and siderophore production [60] by these strains that caused effective colonization of cotton roots by these strains leading to reach more nutrients (Zn, P) [61,62]. The plant growth-promoting abilities of Bacillus strains have already been reported in our previous study [28].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Inoculation with bacterial strains enhances growth and growth-related attributes of cotton, owing to different direct and indirect growth-promoting traits. In present studies, co-inoculation with phosphate and Zn solubilizing strains enhanced growth and yield parameters of cotton crop that might be due to catalase activity, urease activity, phytohormone production, exopolysaccharides production [59] and siderophore production [60] by these strains that caused effective colonization of cotton roots by these strains leading to reach more nutrients (Zn, P) [61,62]. The plant growth-promoting abilities of Bacillus strains have already been reported in our previous study [28].…”
Section: Discussionsupporting
confidence: 56%
“…They solubilized more nutrients and performed more functions according to their capabilities, which favored plant growth and yield attributes. Rafique et al [62] characterized PGPB strains as promising multifarious mineral solubilizers, demonstrating an increase in quinoa's growth and physiology. Li et al [63] also reported that the combined application of mineral solubilizing PGPB strains promoted nutrient availability in soil and root growth of Robinia pseudoacacia through promoting mineral solubilization and enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
“…and Paenibacillus sp.) were also described previously as pathogen controllers inherited from seeds [ 74 , 76 , 95 , 96 , 97 , 98 ]. Additionally, some of these strains were previously identified as part of the seed microbiota in previous studies ( P. tundrae , P. megaterium and P. megaterium ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus (P) is an essential macronutrient for plant survival and reproduction, as a component of nucleic acids, membrane phospholipids and many energy-dependent metabolic processes (Vance et al, 2003). Phosphorus is frequently the most limiting element in soils because it rapidly forms insoluble complexes with cations and has low solubility and poor mobility in soils (Hinsinger, 2001;Rafique et al, 2022). The total amount of P is quite abundant in many soils, ranging from 0.02% to 0.5% (w/w), with an average of about 0.05% (w/w) (Son et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobacteria are plant-associated bacteria that colonize and persist in the proximity of roots or inside the root tissues (Backer et al, 2018). Phosphate-solubilizing bacteria (PSB) have the capacity to convert insoluble inorganic phosphates into soluble forms available to plants (Rafique et al, 2022). The principal mechanism for mineral P solubilization by PSB is associated with the production of low-molecular-weight organic acid anions, which through their hydroxyl and carboxyl groups chelate the phosphate-bound cations to liberate P in soluble forms (Hassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%